Investigation of HNF-1B as a diagnostic biomarker for pancreatic ductal adenocarcinoma - Michelle X. Yang; Ryan F. Coates; Abiy Ambaye; Juli-Anne Gardner; Richard Zubarick; Yuan Gao; Joan Skelly; James G. Liu; Mari Mino-Kenudson (BMC, 2018)
Abstract Background Diagnosing pancreatic ductal adenocarcinoma (PDAC) in the setting of metastasis with an unknown primary remains very challenging due to the lack of specific biomarkers. HNF-1B has been characterized as an important transcription factor for pancreatic development and was reported as a biomarker for clear cell subtype of PDAC. Methods To investigate the diagnostic role of HNF-1B for PDAC, we used tissue microarray (TMA) and immunohistochemistry (IHC) to characterize HNF-1B expression in a large cohort of carcinomas, including 127 primary PDACs, 47 biliary adenocarcinomas, 17 metastatic PDACs, and 231 non-pancreaticobiliary carcinomas. Results HNF-1B was expressed in 107 of 127 (84.3%) of PDACs, 13 of 15 (86.7%) of cholangiocarcinomas, 13 of 18 (72%) of ampullary carcinomas, and 13 of 14 (92.9%) of gallbladder adenocarcinomas. Notably, HNF-1B was expressed in 16 of 17 (94.1%) of metastatic PDACs. Among the non-pancreaticobiliary cancers, HNF-1B was expressed in ~ 77% clear cell carcinomas of the kidney and ovarian clear cell carcinomas. Gastroesophageal, lung, and prostate adenocarcinomas occasionally expressed HNF-1B in up to 37% cases. HNF-1B was completely negative in hepatocellular, colorectal, breast, and lung squamous cell carcinomas. The sensitivity, specificity, positive predictive value, negative predictive value, and accuracy of HNF-1B for primary pancreaticobiliary carcinoma is 84, 68, 66, 85, and 75%, respectively. HNF-1B expression was not significantly associated with overall survival in patients with PDAC, but tumor size ≥2 cm and high tumor grade were significantly associated with worse overall survival in multivariate analyses. Conclusions HNF-1B may be used in surgical pathology to aid the diagnosis of metastatic pancreatic and biliary carcinoma with a panel of other markers to exclude lung, kidney, prostate, and Müllerian origins.